Effect of Soy Protein on the Toughness and Bonding Performances of Cold-Setting Melamine-Urea-Formaldehyde Resin Adhesive - Liang, Jiankun; Zhang, Bengang; Yang, Hui; Meng, Tong; Chen, Chuchu; Li, Huali; Li, Cheng; Wu, Zhigang (BioResources, 2025)
The effects of adding defatted soybean flour (SF) at different stages of the “alkali-acid-alkali” process were studied relative to the viscosity, impact toughness, bonding strength, and water resistance of melamine-urea-formaldehyde (MUF) resin. The results showed that the influence of SF on the strength properties and water resistance of the resin exhibited distinct stage-specific and dosage-dependent characteristics. In the first stage, an appropriate amount of SF (4% to 6%) significantly improved the resin’s viscosity, impact toughness, and bonding strength, demonstrating good toughening and strengthening effects. In the second stage, the addition of SF led to more complex and somewhat unstable effects on viscosity and impact toughness. In the third stage, a moderate amount of SF (2% to 6%) evidently enhanced bonding strength, but high dosages (8% and 10%) resulted in a decrease in water resistance and impact toughness.